Implementasi Kebijakan Penanganan Kawasan Permukiman Kumuh di Kota Gorontalo - Mukharomah, Siti; Aneta, Asna; Isa, Rusli (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The study aimed to discover how the implementation of the Slum Settlement Handling Policy in Gorontalo City is executed using indicators, managing policy processes, managing inter-organizational relationships, and managing both external and internal relations. This study used a qualitative approach with a qualitative descriptive research type. Moreover, the data were collected using observation, interviews, and documentation. Based on the study findings and discussions, the following study conclusions can be drawn: The Implementation of the Slum Settlement Handling Policy in Gorontalo City using indicators such as managing policy processes, managing inter- organizational relationships, and managing internal and external aspects. From an implementation perspective, this policy has been effectively executed in accordance with the provisions of Regional Regulations (Perda) of Gorontalo City Number 19 of 2017 concerning the prevention and improvement of the quality of slum housing and settlements. This regulation is aimed at addressing the issues of slum housing and settlements in Gorontalo City, enhancing the quality of life for the residents, and reducing poverty In handling slum settlement areas, the government has adopted policies involving cooperation and coordination with various relevant agencies, such as relevant departments, provincial government, local government, districts, and sub- districts. This policy aims to develop settlement areas and avoid slum conditions permanently. However, there are challenges to be faced, such as difficulties in implementing development plans due to the lack of coordination and synergy among government agencies and stakeholders. Insufficient resources, including budget constraints and limited infrastructure availability, often hinder development plans.